2020
DOI: 10.21577/0103-5053.20190225
|View full text |Cite
|
Sign up to set email alerts
|

Brazil Nut Oil Extraction Using Subcritical n-Propane: Advantages and Chemical Composition

Abstract: In order to provide an effective and environmentally correct alternative for oil extraction, subcritical n-propane was used under different temperature and pressure conditions to obtain Brazil nut oil. The composition of the oil was determined and compared to the oils obtained by conventional methods. The result of the extraction yield obtained using subcritical fluid extraction (SFE) at 60 °C, 6 MPa and granulometry < 1.40 mm (63.13%) presented minor differences to the yield obtained by Soxhlet extraction (SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…2b) were very similar (PUFA and ALA concentrations around (81% and 59%, respectively). Our results agree well with those of other authors, who used chia seeds from several geographical origins, and applied different extraction methods and operational conditions [7][8][9][10][11][17][18][19][20].…”
Section: Supercritical Co 2 Extractionsupporting
confidence: 92%
See 1 more Smart Citation
“…2b) were very similar (PUFA and ALA concentrations around (81% and 59%, respectively). Our results agree well with those of other authors, who used chia seeds from several geographical origins, and applied different extraction methods and operational conditions [7][8][9][10][11][17][18][19][20].…”
Section: Supercritical Co 2 Extractionsupporting
confidence: 92%
“…Thus far, different solvents (ethyl acetate, acetone, propane, petroleum ether and hexane) and extraction techniques (cold and hot pressing, Soxhlet, Ultrasound-Assisted Extraction and Pressurized Liquid Extraction) have been applied to obtain chia seed oil [7][8][9][10][11]. A viable and eco-friendly alternative to the use of organic toxic solvents is the extraction with supercritical CO 2 (scCO 2 ), which is non-toxic, non-flammable, non-mutagenic and carcinogenic and is abundant and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…Although SUBLDME is wildly used for the extraction of biologically active, lipid, flavoring, or pungent organic compounds in many substances, there are not many studies investigating the effect of the extraction on RBO and phytosterol content. Kamchonemenukool et al [ 101 ] found high phytosterol contents from filter mud discarded from sugar mill extracted using SUBLDME at 20,879 mg/100 g. Guo et al [ 45 ] also reported the phytosterol content of rapeseed cake oil extracted with subcritical 1,1,1,2-tetrafluoroethane (R134a)/butane was 560.19 mg/100 g. Zanqui et al [ 102 ] extracted Brazil nut oil with subcritical n-propane by varying the extraction temperature and pressure, and obtained phytosterol contents ranging from 54.09 to 69.99 mg/100 g. Han et al [ 103 ] also found the phytosterol content of soybean germ oil extracted with subcritical butane at 2772.90 mg/100 g.…”
Section: Resultsmentioning
confidence: 99%
“…Low operation pressure (0.3–1 MPa), energy consumption, and production cost make SBE more economical for large-scale industrial applications than supercritical CO 2 extraction (pressure > 25 MPa) ( Li et al, 2023 ). The application of SBE has been evaluated in extracting oils from red pepper seed ( Liu et al, 2020 , Zhang et al, 2019a ), flaxseed seed ( Wang et al, 2020 ), Brazil nut ( Zanqui et al, 2020 ), and sunflower seed ( Li et al, 2023 , Nimet et al, 2011 ). These SBE oils have shown strong oxidation stability and high bioactive contents.…”
Section: Introductionmentioning
confidence: 99%